Presentation and management of choledocal cyst - Patel, Kiran; Patel, Ankit B. (International Surgery Journal, 2019)
Background: Choledochal cyst is congenital disease of biliary tract. There are five main types of choledochal cyst with few recognised sub types. The etiology of choledochal cyst is unclear. Methods: Author here randomly studied patients from May 2012 to June 2015 from surgical department of the institute. Radical excision of cyst wall with reconstruction of biliary tract using a Roux-en-Y loop of jejunum is the treatment in a patient. Results: Out of 30 patients, 24 were discharged as routine procedure. Out of 30, six patients had complications which were treated and cured, only one patient died due to ARDS post operatively. Conclusions: Choledochal cyst is congenital disease. In the past, it was treated by drainage procedure. But nowadays, it is treated by radical excision with Roux-en-Y hepaticojejunostomy with minimum mortality. In present study, 3.33% (one patient) death occurred. So, in planned surgery results are good but in emergency (in this study one patient died) death can occur, inspite of good surgical approach.